Boar Reproduction Fundamentals and New Biotechnological Trends - Bonet, Sergi; Casas, Isabel; Holt, William V.; Yeste, Marc.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Latent knowledge in the field of pig reproduction is vast but scattered, making it difficult to take in all information at a glance. Moreover, nascent branches in biotechnology cannot grow if deprived of roots. The book Boar Reproduction: Fundamentals and New Biotechnological Trends links the past, the present and the emerging scientific research fields on reproductive biotechnology, offering a rigorous but easy to follow compilation of topics, from (3z(Bold favorites(3y (Bto the latest advances. The book is organized in three parts. The chapters of the first and second part cover various biological aspects of boar spermatozoa within the male, and within the female environments, respectively. The most common laboratory and artificial insemination techniques are discussed in the third part. As an additional feature, some chapters focus on the basis of a technology transfer to bring research expertise from basic science to the market, making the information provided in this book suitable for academic, research and other professional applications.s
Boar Spermatozoa Within the Male Genital Tract -- Boar Spermatozoa Within the Male Genital Tract -- Artificial Insemination (AI) Technologies on Pigs.
Keywords: Life sciences; Biotechnology; Animal genetics; Animal Physiology; Life Sciences; Animal Genetics and Genomics; Animal Physiology; Biotechnology